Penggunaan Canva Sebagai Media Pembelajaran dalam Meningkatkan Kemampuan Berbicara Bahasa Inggris - JF, Nur Hidayat (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This study aims to analyze the effect of using the Canva media application in improving English speaking skills. This research was conducted using library research-based research methods (library research), with data analysis techniques using descriptive analysis techniques. The results of the study explain that the classroom action research procedure begins with the procedure for identifying learning problems encountered by educators in class, then carrying out problem formulation, conducting research, analyzing data and writing reports. Implementation is carried out through four stages, namely planning, implementation, observation, and follow-up. Keywords: Learning media, Canva application, skills, speaking, speaking English